2019
DOI: 10.1108/bfj-01-2019-0051
|View full text |Cite
|
Sign up to set email alerts
|

Motivations to consume ecological foods in alternative food networks (AFNs) in Southern Spain

Abstract: Purpose The purpose of this paper is to identify the motivations to consume ecological foods in alternative food networks (AFNs). Design/methodology/approach In total, 150 questionnaires were applied; the questionnaire was adapted from Food Choice Questionnaire (Steptoe et al., 1995). Data were analyzed by means of multivariate statistics with factor and cluster analysis. In order to identify statistical differences (p<0.05), Kruskal–Wallis and Mann–Whitney nonparametric tests were performed. Findings T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
4
6
0
1
Order By: Relevance
“…Findings shown in Table 4 are in agreement with the literature, where the typical profile of the consumer of ecolabeled food products is women, with a high educational level and middle‐aged (Y. S. Chen, 2010; Escobar‐López et al 2017, 2019; Lee & Yun, 2015; Mohamad et al, 2014; Wu et al, 2014).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Findings shown in Table 4 are in agreement with the literature, where the typical profile of the consumer of ecolabeled food products is women, with a high educational level and middle‐aged (Y. S. Chen, 2010; Escobar‐López et al 2017, 2019; Lee & Yun, 2015; Mohamad et al, 2014; Wu et al, 2014).…”
Section: Resultssupporting
confidence: 87%
“…The number of these factors (variables) used for the classification of consumers in this study (8) is in line with that of other studies that used between 5 and 9 factors (Escobar-López et al, 2017;Lee & Yun, 2015;Mohamad et al, 2014;Stolz et al, 2011). However, this number of variables is lower than that applied by other authors (Escobar-López et al, 2019;Zander & Hamm, 2010).…”
Section: Latent Class Approachsupporting
confidence: 86%
“…This coincides with what other authors have established about these spaces being feminized [13]. Several works have reported that women have more pro-environment attitudes and take a more active part in this type of initiatives, being described as "female citizen consumers" [13,45,78]. For example, Danish women (in their consumption of differentiated foods) showed a higher affinity with the Civic, Domestic and Market worlds [79].…”
Section: Influence Of the Socioeconomic Factorssupporting
confidence: 84%
“…Although the potential importance of individual consumers and communities is noteworthy [44], the consideration of the rest of actors involved in food chains (in order to correctly understand their signifiers and practices) becomes of relevance. However, the main gap of those studies is that production, consumption and retail channels [16,29,40,[45][46][47][48] and organizers [25] have been analyzed separately. Therefore, to obtain a global vision of AFNs, behaviors, motivations and perceptions of all involved actors should be taken into account [4].…”
Section: Short Food Supply Chainsmentioning
confidence: 99%
See 1 more Smart Citation